2022
DOI: 10.3389/fphar.2022.821344
|View full text |Cite
|
Sign up to set email alerts
|

JAK/STAT Signaling: Molecular Targets, Therapeutic Opportunities, and Limitations of Targeted Inhibitions in Solid Malignancies

Abstract: JAK/STAT signaling pathway is one of the important regulatory signaling cascades for the myriad of cellular processes initiated by various types of ligands such as growth factors, hormones, and cytokines. The physiological processes regulated by JAK/STAT signaling are immune regulation, cell proliferation, cell survival, apoptosis and hematopoiesis of myeloid and non-myeloid cells. Dysregulation of JAK/STAT signaling is reported in various immunological disorders, hematological and other solid malignancies thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(57 citation statements)
references
References 194 publications
(224 reference statements)
0
46
0
Order By: Relevance
“…In the PPI network, we found that IL-1β, IL-6, TNF-α, IL-10, IL-17A, IL-21, and IL-22 interact directly and indirectly with proteins that participate in the NF-κB, MAPK, PI3K-Akt, mTOR, FoxO, and Jak-STAT signaling pathways. The largest number of these pathways contribute to the regulation of proliferation, differentiation, growth, apoptosis, angiogenesis, cell survival, adhesion, migration, invasion, epithelial-mesenchymal transition, resistance to oxidative stress, metabolism, autophagy, inflammation, and metastasis processes that contribute to carcinogenesis or tumor progression [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Additionally, we found that TNF-α interacts with proteins that are involved in the NF-κB, MAPK, mTOR, and apoptosis signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In the PPI network, we found that IL-1β, IL-6, TNF-α, IL-10, IL-17A, IL-21, and IL-22 interact directly and indirectly with proteins that participate in the NF-κB, MAPK, PI3K-Akt, mTOR, FoxO, and Jak-STAT signaling pathways. The largest number of these pathways contribute to the regulation of proliferation, differentiation, growth, apoptosis, angiogenesis, cell survival, adhesion, migration, invasion, epithelial-mesenchymal transition, resistance to oxidative stress, metabolism, autophagy, inflammation, and metastasis processes that contribute to carcinogenesis or tumor progression [ 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Additionally, we found that TNF-α interacts with proteins that are involved in the NF-κB, MAPK, mTOR, and apoptosis signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that PRF1 mediates tumor-infiltrating T lymphocytes (TIL) oligoclonal amplification-enhanced Th1 (helper T cell type I)-skewed cellular immunity during nivolumab treatment ( 53 ). STAT1 (signal transducers and activators of transcription 1) is a family of cytosolic proteins that, upon activation, can translocate to the nucleus and bind DNA, which has dual signal transduction and transcriptional control functions ( 54 , 55 ). Hypermethylation in the promoter region of the SOCS3 gene was discovered to reduce SOCS3 protein expression in some CM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated STAT5 inhibited the transcription factor p21, a cell-cycle inhibitor, leading to increased proliferation of ovarian carcinomas ( 37 ). Furthermore, studies on JAK2 V617F mutations, acquired somatic mutations often found in patients with myeloproliferative cancers, revealed that STAT5 over-activation can also cause increased cell proliferative behavior in non-myeloid cells such as mammary cells ( 38 ). A point mutation in JAK2 allowed constitutive activation of JAK2 in epithelial mammary cells, which led to hyperactivation of STAT5 that eventually enhanced the proliferation of epithelial memory cells.…”
Section: Signal Transductionmentioning
confidence: 99%